Hypothesis about Transdifferentiation As Backbone of Malignancy - Piechowski, Jean (Frontiers in Oncology, 2017)
Background. Cancer is mainly watched through the prism of random mutations and related corruption of signaling pathways. However, it seems puzzling to explain the tumor organization and the pugnacity and steady evolution of the tumorous disease, with moreover a systematic ascendancy over the healthy tissues, only through stochastic genomic alterations. Malignancy specific properties. Considering the core characteristics of cancer cells, it appears that two major sets of properties are emerging, corresponding to well-identified physiological phenotypes, i.e., 1) the trophoblastic logistical functions for cell survival, protection, expansion, migration, and host-tissue conditioning for angiogenesis and immune tolerance, and 2) the sexual functions for genome maintenance. To explain the resurgence of these trophoblastic and sexual phenotypes, a particular cell reprogramming to be called “malignant transdifferentiation” in view of its key role in the precancer-to-cancer shift, appears to be a convincing hypothesis. Perspectives. The concept of malignant transdifferentiation, in addition to oncogenic mutations, would determine a more rational approach of oncogenesis and would open so far unexplored ways of therapeutic actions. Indeed, the trophoblastic phenotype would be a good candidate for therapeutic purposes because, on the one hand it covers numerous properties that all are vital for the tumor, and on the other hand it can be targeted with potentially no risk of affecting the healthy tissues as it is not expressed there after birth.